STUDENTS’ ATTITUDE TOWARDS ORAL PRESENTATION IN VIRTUAL LEARNING AT ENGLISH EDUCATION STUDY PROGRAM OF PATTIMURA UNIVERSITY - Rosina F. J. Lekawael; Ayuni Abdullah Reniwuryaan; Hanafi Bilmona (English Review: Journal of English Education, 2023)
Studies about an attitude toward learning English have been conducted almost everywhere because of its important influence on the English learning process. The attitude can be categorized into three components namely cognitive, affective/emotional, and behavioral. The study is focused on the emotional component which covers the person’s emotions and feeling towards an object. It can directly affect one’s preferences in order to stand for or against or to like or dislike something. Due to the pandemic situation where all the subjects must be done virtual, the researcher attempts to explore what are students’ emotional attitudes toward the virtual oral presentation. The researcher finds it interesting since virtual learning is an uncommon method for students, especially in doing an oral presentation as well as the novelty of the previous related study. The research objective is to find out the students’ emotional attitudes towards oral presentation in virtual learning, especially in the fifth semester of the English education study program at Pattimura University. This study applied a survey as a research design by using a Questionnaire and Interview. The subject of this study consists of fifteen students who enrolled in SLA class. The result of the questionnaire showed that most students in the second language acquisition (SLA) class held a positive attitude toward the virtual oral presentation. The majority or 12 students (80%) strongly agreed that the oral presentation in virtual learning is more fun and preferable. On the other hand, 11 students (73.3%) strongly agreed that it reduces their anxiety level and also improves their self-confidence. In conclusion, it benefits so much to improve their motivation in English virtual learning compared to face-to-face oral presentations. In a face-to-face class, they had high speaking anxiety by having a great fear of getting involved in a conversation, great fear of the audience, and a great fear of failure. In addition, further researchers can focus on the technology application in virtual learning and its impact on students’ language ability as the novelty element of this study.